Determinación del contenido total de hongos en doce especies vegetales cultivadas en Ecuador. - Medina Caiminagua, Mariuxi Lissette (2015)
The use of healing plants is one of the therapies medical more ancient and widespread that is remote to the prehistoric times, and today are also used in the preparation of herbal medicine with options to cure diseases. The determination of fungi test was conducted in the laboratory of pilot plant of Pharmacy (PPF) and the laboratory of Microbiology of the academic Division of chemical sciences and health, of the Technical University of Machala, in each area were performed different tasks: laboratory PPF, was carried out the treatment of the leaves of the plant species and the microbiology laboratory area where the determination of fungi in plant species, was carried out using culture medium called Sabouraud agar more vegetable sample.